Behavioural responses of non-breeding waterbirds to marine traffic in the near-shore environment. Issue 4 (2nd October 2021) - Jarrett, David; Calladine, John; Cook, Aonghais S. C. P.; Upton, Andrew; Williams, Jim; Williams, Stuart; Wilson, Jared M.; Wilson, Mark W.; Woodward, Ian; Humphreys, Elizabeth M.
ABSTRACT: Capsule: Recording of behavioural responses to ferry traffic for 11 target species showed that Red-throated Diver Gavia stellata, Slavonian Grebe Podiceps auratus, and Black-throated Diver Gavia arctica were most likely to react to passing vessels. Aim: To provide information on how responses to marine traffic vary between waterbird species to inform marine spatial planning and environmental impact assessments in the near-shore environment. Methods: We recorded behavioural responses to ferry traffic for 11 target species in near-shore waters: Common Eider Somateria mollissima, Goldeneye Bucephala clangula, Long-tailed Duck Clangula hyemalis, Velvet Scoter Melanitta fusca, Red-breasted Merganser Mergus serrator, Black-throated Diver, Great Northern Diver Gavia immer, Red-throated Diver, European Shag Gulosus aristotelis, Slavonian Grebe and Black Guillemot Cepphus grylle . Responses were analysed using generalized linear models and mixed models. Results: Red-throated Diver, Black-throated Diver and Slavonian Grebe were the most likely species to exhibit a response to passing vessels. While Red-throated Divers and Slavonian Grebes were highly likely to flush, Black-throated Divers and Great Northern Divers rarely took flight, instead favouring swim or dive responses. In rougher sea conditions birds were more likely to take flight, and the propensity to respond declined across the wintering period. Conclusions: This research provides comparative evidence on the behavioural responses of waterbirds to marine traffic. The results support previous studies which highlighted the high sensitivity of diver species to disturbance and provide new evidence that Slavonian Grebe may also be a high sensitivity species.